Postpurchase dissonance pada pengguna iphone ditinjau dari kepribadian Tipe A dan Tipe B - Risma Evie Kusrina; Muhamad Salis Yuniardi; Alifah Nabilah Masturah (Fakultas Psikologi, 2019)
In consumer behavior, it followed by post-purchase evaluation. When in the evaluation, there appears a doubt about the purchase decision on a product, and then an individual must be experiencing a post-purchase dissonance. The product used in this study is the iPhone. As for the factors that can influence post-purchase dissonance, one of them is the tendency of individual anxiety, which is caused by personality type. This study aims to determine the differences in iPhone users’ student with type A and type B personalities in experiencing post-purchase dissonance. The analysis used causal comparative and determination of the subject used purposive sampling. The research subjects were iPhone users’ students of Muhammadiyah Malang University, amount 125 subjects. This study used a post-purchase dissonance scale, also type A and type B personality scale. The analysis in this study used an independent sample t-test. The results showed that there was no difference in post-purchase dissonance in terms of type A and type B personality patterns with a significance value of 0.352 and p = 0,05 (0,352 > 0,05). Keywords: Post-purchase dissonance, Type A and type B personality, iPhone users’ Student.